2011
DOI: 10.1002/elan.201100195
|View full text |Cite
|
Sign up to set email alerts
|

Flow Injection Analysis of Ethambutol in Antituberculosis Drugs Using a Graphite‐Paraffin Electrode as Amperometric Detector

Abstract: A graphite-paraffin composite electrode has been used for the determination of ethambutol, an antituberculosis drug, in pharmaceutical samples by anodic oxidation. Voltammetric studies were used to characterise the electrochemical behaviour of the ethambutol in different pH solutions (3.0, 8.0 and 12.0). Quantification was carried out using amperometric detection. The detector was assembled in a flow injection apparatus and operated at + 1.1 V (vs. Ag/AgCl (NaCl,sat) ). The conditions for the best electrodes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
0
8
0
1
Order By: Relevance
“…Glassy carbon (Palomeque andOrtíz 2007, Pfaffen et al 2013), paraffinated graphite (Perantoni et al 2011), carbon paste (Dejmkova et al 2013), boron-doped diamond (Wangfuengkanagul et al 2004) and, particularly, gold (Palaharm et al 2003, Charoenraks et al 2004, Codognoto et al 2010) and screen-printed gold (Masawat and Slater 2007) were reported electrode materials. Electrode modification with metalloporphyrin (Gong et al 2003), cyclodextrin (Lomillo et al 2005), carbon nanotubes ), among others (Won et al 2013), have been reported.…”
Section: Amperometric Methodsmentioning
confidence: 97%
“…Glassy carbon (Palomeque andOrtíz 2007, Pfaffen et al 2013), paraffinated graphite (Perantoni et al 2011), carbon paste (Dejmkova et al 2013), boron-doped diamond (Wangfuengkanagul et al 2004) and, particularly, gold (Palaharm et al 2003, Charoenraks et al 2004, Codognoto et al 2010) and screen-printed gold (Masawat and Slater 2007) were reported electrode materials. Electrode modification with metalloporphyrin (Gong et al 2003), cyclodextrin (Lomillo et al 2005), carbon nanotubes ), among others (Won et al 2013), have been reported.…”
Section: Amperometric Methodsmentioning
confidence: 97%
“…The composites reached were then compressed and sealed inside plastic syringes, being the electric contact made by metallic wires, as illustrated in Figure 1. The working electrode consisted of different proportions between graphite particles and paraffin (from 65 to 80% m/m) solid dispersion, prepared as previously described in Perantoni et al 41 In brief, suitable amounts of paraffin and graphite were mixed in small glassy cups keeping constant masses to reach every assessed proportion graphite/insulator; this mixture was then heated at 60°C and inserted in a suitable plastic syringe, providing, this way, rods with 0.5 cm length. Copper wires were applied to obtain electrical contact.…”
Section: Composite Electrodes Preparationmentioning
confidence: 99%
“…Recently literature shows an interesting citation regarding solid wax composite electrode applied to the determination of ethambutol in pharmaceuticals by flow analysis systems. 41 This article intends to describe some uses for the graphite-paraffin electrode composite applied in the determination of complex B vitamins (vitamin B 2 , riboflavin, and vitamin B 6 , pyridoxine) in aqueous media by voltammetric techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is very important to develop a simple, sensitive, reliable and environmentally friendly method for the determination of ethambutol. Several analytical techniques were reported including, potentiometry, Fourier-transform infrared spectroscopy, ultraviolet spectroscopy, fluorescence spectroscopy, capillary electrophoresis, supercritical fluid chromatography, mass spectrometry, high performance liquid chromatography and electroanalytical methods [5,7,[9][10][11][12][13]. However, attention has been given to electrochemical techniques recently owing to their operational simplicity, sensitivity, cost effectiveness, absence of extensive sample pretreatment and suitability for onsite analysis due to their portability.…”
Section: Introductionmentioning
confidence: 99%